(untitled) (Indian Journal of Animal Production and Management, 2024)
A case series study was conducted from December 2022 to August 2023 in cattle referred to the Veterinary Dispensary Peddaputta village of Kadapa district. Total 6 cross bred cattle were diagnosed and most of them referred with swelling at the mandibular region showing leakage of pus and it was diagnosed as bovine Actinomycosis or lumpy jaw condition. Haematology revealed significant erythrocytopenia, higher PCV, lower haemoglobin concentration, significant leucocytosis with neutrophilia, presence of a greater number of immature neutrophils and decreased lymphocyte count. With the surgical intervention granulomatous tissue and pus was removed, and antibiotics like long acting Terramycin injection two doses within 48 hours, along with oral administration of Potassium Iodide and external dressing of wound with 2% povidone iodine. The animal recovered successfully within 12 days of post treatment.